Reporting verb in research projects of EFL English major students - CHATTRAPORN JUNNAK; ANCHALEE VEERACHAISANTIKUL (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: The current study set out to determine 1) which types of reporting verbs are most commonly used by EFL English major students in their research projects and 2) which types of reporting verbs are most commonly used by this population.Method: 52 research projects written by English as a Foreign Language (EFL) students majoring in English were chosen and analyzed to achieve the study’s goals. Furthermore, reporting verbs were categorized according to Francis, Huston, and Manning’s (1996) work.Findings: As the results indicated, "show," "find," "present," "analyze," and "state" were the five reporting verbs used most frequently. The results showed that after classifying the reporting verb groups, the ARGUE verb group comprised 50% of all reporting verb groups, followed by the THINK verb group (18.75%), SHOW verb group (12.5%), FIND verb group (12.5%), and ADD verb group (6.25%), respectively.Implications/Novel Contribution: The purpose of this research is to educate writers to make more informed decisions when selecting reporting evidence for academic writing or research projects. From a theoretical perspective, this is just the tip of the iceberg when it comes to investigating the potential benefits of evidentiality for language users beyond simply identifying the origin of a piece of information. It could help guide future research and provide a basis for new findings. There is still room for research into topics like the purposes of different kinds of evidence, genre conventions, and the application of evidence in different types of writing.